BUDAYA KERJA, KOMITMEN PEGAWAI DAN KINERJA PEGAWAI - Thianggor Siregar (Universitas Riau, 2015)
Work Culture, Employee Commitment and Performance Officer. This study aimed to analyze the effect of work culture and employee commitment to employee performance. The population is all employees working in agencies Executing Agency for Food Security and Agricultural Extension Pekanbaru many as 72 people. Collecting data using questionnaires. Data analysis methods used include test research instruments, test classic assumptions and hypothesis testing using multiple linear regression analysis. The results showed in the F test (simultaneous) that the work culture, and employee commitment to significantly affect the performance of employees with F sig value 0,000 <0,05 and F count 18.193. T test (partial) shows the work culture significantly affect the performance of employees with t sig value 0,000 <0,05 and 5,844 t value, and commitment employees have little influence on employee performance with sig t 0.079> 0.05 and values t -1.781.